EFFECT OF FERTILIZATION, ROOTSTOCKS AND GROWTH STIMULANT ON GROWTH OF Citrus limon L. SAPLING. - & Khalil, Alkhafaji; & Khalil, Alkhafaji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A research was carried out in the lath house of the College of Agricultural Engineering sciences / University of Baghdad / Al-Jadriyah, for three growth seasons Spring 2017, Fall 2017 and Spring 2018 to study the effect of different fertilization methods, were Fertigation (Ft) , Foliar application (Fa), traditional soil fertilization (Fo) and growth stimulant with two concentrations 0 (D0) and 1.5 mg.L-1 (D1) on the growth of local Citrus limon L. Saplings grafted on Citrus aurantium L. (So), C. volkameriana (Vo), and Citrumello (Co). Saplings were cultivated in 10 kg plastic containers. A factorial experiment was carried out according to the Nested-Factorial Experimental design. Results indicated foliar application (Fa) superiority, followed by Fertigation (Ft) in plant height, rootstock and scion diameter, while the number of shoots increased significantly using (Ft). Lemon trees grafted on (So) showed superiority in plant height, while trees grafted on (Vo) recorded higher rates in rootstock, scion diameter, and shoot number. Plants fertilized with (Fa) surpassed in nutrient use efficiency (NUE) of N, P, K they were 1.18, 0.43 and 1.30 g.dw -1, respectively. (Vo) indicated highest value in (NUE) of N, P, K elements in plants (1.32, 0.48 and 1.45 g. dw -1) in comparison to So and Co. The Fa * Vo * D0 treatment increased significantly rootstock stem diameter (73.15 and 126.03%), while the highest rate in plant height was recorded by Fa * So* D0 (111.19%.) The highest increase rate of shoot number (483.9%), was by Ft * So * D1. The treatment Fo * Co * D1, gave the highest carbohydrate (4.92%).